До питання фольклоризму та фольклоризації творчості трудових мігрантів - Крамар, Р. (Народна творчість та етнографія, 2007)
The topicality of the research is caused by the lack of study of creative activities of the Ukrainians who are hunting for a job abroad. Prose, poetry, small genres are not the object of the thorough research yet. At the same time folkloristic processes flow lively among this group of people. This thought is proved by author’s own fieldwork. Dramatic peculiarities of migrants’ creativity (homesickness, loneliness, nostalgia) help laborers to bear their lives. Some of the bright examples of migrant folklore (poems, jokes, and a vocabulary) are given in the article as well.